Decellularized human dermis vs. standard care in two diabetic foot ulcers: A comparative case report - Verandani, Kanchan; Banks, Jaminelli; Penumarthi, Krishna Sai (Journal of the Foot & Ankle, 2025)
Objective: To describe healing trajectories in two neuropathic diabetic foot ulcer cases—one treated with decellularized human dermis (DHD) and one with moist wound management (MWM). Methods: After a two-week optimization period, two adults with long standing diabetes and plantar ulcers were managed weekly for 12 weeks. Case 1 received a single 4 × 4 cm DHD graft combined with non-adherent dressings, and case 2 received gauze-based MWM alone. Wound area was quantified using digital planimetry. Results: Case 1 achieved an 80% area reduction by week 4 and achieved full epithelialization at week 8. Case 2 showed a 7.8% area reduction by week 2, a transient 21.6% area increase between weeks 3 and 5, and reached 68.6% reduction by week 12 without closure. No adverse events occurred. Conclusion: The results of our study suggest that DHD may accelerate closure compared with standard care. Due to the small sample size, randomized controlled studies with longer follow-up are essential. Level of Evidence V; Case report.